Endoscopic transfer of the flexor hallucis longus tendon: technical tip to harvest a long graft - Soares Baumfeld, Daniel; Soares Baumfeld, Tiago; Dutra Macedo, Benjamim; Oliveira Pimenta, Felipe; Souza da Silva, Felipe; Augusto de Souza Nery, Caio (Journal of the Foot & Ankle, 2025)
The Achilles tendon (AT) is the toughest and most robust tendon in the human body. However, it is the most frequently injured. Several surgical techniques are described in the literature for treating chronic or complex injuries. Some of them use tendon transfers of the peroneus brevis, flexor digitorum longus and flexor hallucis longus (FHL). The FHL tendon transfer can be performed endoscopically (minimally invasive), a reliable method for treating AT ruptures. The objective of this study was to describe a technical tip to allow surgeons to harvest a longer tendon graft using a tendon stripper without the need for additional portals. Level of Evidence V; Therapeutic Studies; Expert Opinion.